Utilisation des espèces spontanées dans trois villages contigus du Sud du Burkina Faso - Guigma, Y.; Zerbo, P.; Millogo-Rasolodimby, J. (Tropicultura, 2012)
Use of Wild Plants Species in Three Adjoining Village Southern Burkina Faso. Wild species are very important for people in developing countries. To enrich the knowledge of useful wild species, series of ethnobotanical surveys was conducted in three adjoining villages of southern Burkina Faso. This survey has permitted to identify 147 species distributed in 117 genera and 52 families. Woody species represent 60% and grass 40%. Fifty percent of the species used belong to seven families: Poaceae, Caesalpiniaceae, Combretaceae, Mimosaceae, Rubiaceae, Fabaceae and Anacardiaceae. Ninety-seven species are used in medicines, 47 for crafts, 46 for cattle feeding, 40 for human nutrition and 21 to provide fire. In all plants use categories, the calculation of index values showed that there are species that are used more than others. Thus, Sarcocephalus latifolius is the species most commonly used in medicines, Parkia biglobosa in human nutrition, Afzelia africana in cattle feeding, Vitellaria paradoxa in crafts and Detarium microcarpum in wood fuel. The evaluation of the diversity of use revealed that wood species have high diversity of uses than herbaceous. V. paradoxa is the species most diversely used. The top five most used species are V. paradoxa, P. biglobosa, Khaya senegalensis, Tamarindus indica and A. africana. The results of this study provide a database to assess the availability and the evolutionary trend of species widely used in the locality.